Tecnologías aplicadas al Cultivo de Cacao Fino de Aroma en el Departamento de Santander para Exportación a Estados Unidos (2022)
The department of Santander, has great factors that make it stand out for maintaining its cocoa productions at the top, managing to sustain an exceptional harvest and post-harvest process, because it has been identified as a major producer at national level, it has also managed to stand out for its demands in international markets, the productions of Santander are highly required for having a cocoa with particular characteristics of aroma and flavor, allowing to lead to a direction of growth in the productions and good management of product care by farmers. Allowing to go further, information is collected about which implementations of technological innovations favor cocoa productions and work as support to farmers, directing to look for ways to generate better strategies to continue to maintain high productivity and good demand in the markets. With the following research it will be proposed which technologies could be applied to cocoa productions, being able to identify which benefits will be reflected in the implementation of technological innovations that will allow to promote agriculture for the department in a competitive way and with great performance, focusing on the objective of improving the quality of production and guarantee good product to national and international markets, as well as the fulfillment of a process from cultivation to export where restrictions imposed by the United States Department of Agriculture for the import of this product will be handled.